Risk and outcomes of healthcare-associated infections in three hospitals in Bobo Dioulasso, Burkina Faso, 2022: A longitudinal study - Arsène Hema; Satouro Arsène Somé; Odilon Kaboré; Soufiane Sanou; Armel Poda; Ziemlé Clément Meda; Abdoul Salam Ouedraogo; Léon Savadogo (PLoS ONE, 2025)
Background Healthcare-associated infections (HAIs) are one of the most common adverse events in healthcare and represent a major public health problem. The present study was conducted to analyze the incidence, risk factors, and outcomes of HAIs through active surveillance in three hospitals in the city of Bobo Dioulasso, Burkina Faso. Methods A prospective, longitudinal, multicenter study was conducted from May 1 to November 30, 2022, in two district hospitals (Do and Dafra) and the Sourô Sanou Teaching Hospital (CHUSS), Burkina Faso. Consenting patients hospitalized for reasons other than infection, cancer, immunosuppression in the postoperative care ward of Do or of Dafra district hospitals, intensive care unit (ICU)/CHUSS, neonatal ward/CHUSS, and gynecology and obstetrics postoperative care ward/CHUSS during a 2-month inclusion period in district hospitals and 4 months for CHUSS wards. For this study, we used the operational definitions of the French Technical Committee for Nosocomial Infections and Healthcare-associated Infections, with slight modifications. Logistic regression was used to analyze risk factors of HAIs. Results Of the 664 patients enrolled, 166 experienced an HAI, with a cumulative incidence rate of 25% (95%CI: 21.7%–28.3%) or an incidence density rate of 36.7 per 1000 patient-days (95% CI: 31.7–42.9). Surgical site infections (SSI) (44%), followed by neonatal infections (42%) were the most common HAIs. Enterobacterales represented 60% of the bacteria identified in HAIs, and 38.9% of them were extended spectrum β-lactamase (ESBL) producers. Factors associated with HAIs were admission in the neonatal ward (aOR = 6.6; 95%CI:1.1–40.2), ICU (aOR = 3.3; 95%CI:1.3–8.5), previous hospital stay longer than two days (aOR = 2.0; 95%CI:1.2–3.3), or male sex (aOR = 1.8; 95%CI:1.1–3.0). In addition, HAIs were associated with longer follow-up, hospitalization, and mortality (18.1%; 95% 95%CI:12.1–24.4). Deaths were only recorded in the ICU and neonatal ward, with case fatality rates of 45.4% (95% 95%CI: 27.5–63.4) and 21.4% (95% 95%CI: 11.6–31.3), respectively, p = 0.019. Conclusions The incidence of HAIs was relatively high in the three hospitals in Bobo Dioulasso, Burkina Faso. It is essential to implement rigorous protocols for patient management, to reduce the incidence of HAIs and the spread of resistant pathogens in general and Enterobacterales in particular.